THE IMPORTANCE OF SELF-CONFIDENCE IN COMMUNICATION (Proceedings of International Conference on Modern Science and Scientific Studies, 2023)
In this era, self-confidence is considered to be one of the key factors on almost every field, especially it is even more valued while communicating with people around you, regardless of the social context. Another key secret of believing in yourself is not to force yourself to do something, but be genuinely interested in what you are doing and you can see how confident you will be after trying to do something you love.